Nanoemulsions of essential oil of Zanthoxylum alatum for protection against Meloidogyne incognita - Ranjeet Kumar; Tushar Kanti Dutta; Abhishek Mandal; Supradip Saha; Anirban Dutta; Aditi Kundu (Journal of Taibah University for Science)
Zanthoxylum alatum is one of the most important aromatic plants, possessing multifunctional biological activities. In the present investigation, essential oil (EO) of Z. alatum fruits was formulated applying nanotechnological interventions to develop stable nanoemulsions (NEs), and characterised for emulsion stability, diameter, polydispersity index (PDI), zeta potential. The developed NEs displayed a mean particle size of 48.21- 89.10 nm, a PDI of 0.39-0.66 and a zeta potential of  > -20.06 mV. Chromatographic analysis of the EO showed linalool (49.94 ± 0.8%), DL-limonene (40.51 ± 0.8%) and β-myrcene (4.27 ± 0.3%) as the main compounds. Nematicidal efficacy of the NEs showed LC50 ranging 49.9-82.5 µg/mL against Meloidogyne incognita at different time intervals. Molecular modeling revealed the most favourable binding complexes of linalool oxide-odr 1 (−36.68 kcal/mol) and linalool oxide-odr 3 (−23.36 kcal/mol), could be responsible for nematicidal action. Linalool also formed stable complexes (−29.46 and −22.45 kcal/mol) with both the proteins. Z. alatum EO could be exploited as bio-nematicide for the management of M. incognita.